Identifying basic infrastructure priorities for slum management through analytical hierarchy process (AHP): A local government perspective - Husna Tiara Putri; Nabila Salsabila (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Padang, as a national activity center, continues to face serious challenges related to urban slum settlements, primarily due to the limited provision of basic infrastructure. While infrastructure provision is considered one of the most effective strategies to address these issues, its implementation remains difficult due to the varying perceptions among government stakeholders responsible for infrastructure development. In this context, identifying priority infrastructure becomes crucial. Methods: This study aims to identify infrastructure priorities for slum upgrading using a mixed-methods approach. The analysis incorporates the perceptions of seven key stakeholders from the local government, employing the Analytical Hierarchy Process (AHP) alongside qualitative descriptive methods based on interviews and field observations. Findings: The results reveal that the prioritized infrastructure components, in order of importance, are drainage, clean water, wastewater management, solid waste management, neighborhood road improvement, and fire protection. These priorities may serve as a guideline for the Padang City Government in realizing a city that is progressive, safe, clean, orderly, inclusive, and respectful of local wisdom. Novelty/Originality of this article: This research offers a unique contribution by presenting infrastructure provision priorities from the perspective of local government—an aspect that remains underexplored in slum settlement studies.